Conductance through two quantum dots in a ring: Magnetic flux dependence - Apel, V.M. (2006)
The conductance of a double-dot system in a ring threaded by a magnetic flux is studied. The ring is connected to two leads in such a way that each dot is embedded in one arm of the structure. The currents going through each arm of the ring are determined by the Aharonov-Bohm effect and the dot charging effects. The conductance for different values of the magnetic flux is obtained as a function of the gate potentials applied to the dots, for two situations: when the dot level energies are equal, ΔE = 0, and when they are different but with ΔE smaller than the Coulomb interaction U. The conductance shows quite distinct behavior according to having a finite or zero magnetic flux threading the ring. The system presents S = 1/2 and S = l Kondo phenomena for no magnetic flux and is in the S = 1/2 Kondo regime in the case of half a quantum of magnetic flux.